Wear Analysis of Crank Slider Mechanism based Stationary Clearance Link Model - Rufei Yu; Wei Chen (Jixie chuandong)
Wear is one of the main causes of the failure of mechanical equipment and mechanical parts. The coupling between wear and dynamic response of system has an important effect on the performances of mechanism. A series of parametric studies are carried out based on a simplified model of revolute reaction force， and the dynamical model of slider-crank mechanism is built through combining with the d'Alembert's principle. The distribution of contact pressure is obtained by using the Winkler elastic foundation model. The wear depth of revolute clearance pair is calculated using Archard model，and the coupling analysis framework between wear and dynamics of slider-crank mechanism with clearance is built. It is found that the coupling model of wear calculation has not only comparative solution precision but also high computation efficiency by comparing with the finite element method（FEM）.